2023
DOI: 10.3390/children10020268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Remineralizing Agents on Shear Bond Strength of Orthodontic Brackets—In Vitro Study

Abstract: Orthodontic treatment can be effective only with the proper adhesion strength of the bonded elements on the teeth. The aim of the study was to analyze the influence of different remineralization products on the brackets (Evolve Low Profile Brackets 0.022 Roth prescription (DB Orthodontics Ltd., Silsden, England) shear bond strength (SBS)). In all, 40 teeth were investigated for this study; n = 30 demineralized (immersed in 0.1% citric acid for 30 min, twice a day, for 20 consecutive days) and n = 10 immersed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…[ 19 , 20 ] However, the research findings in practice found that remineralization product application (toothpaste and tooth gel) has no influence on micro-SBS which is in accordance with the results stated by other studies. [ 26 , 27 , 28 ] In fact, Fluoride at low concentrations has been proven to promote remineralization across orthodontic brackets with an unimportant effect on SBS. [ 29 , 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 , 20 ] However, the research findings in practice found that remineralization product application (toothpaste and tooth gel) has no influence on micro-SBS which is in accordance with the results stated by other studies. [ 26 , 27 , 28 ] In fact, Fluoride at low concentrations has been proven to promote remineralization across orthodontic brackets with an unimportant effect on SBS. [ 29 , 30 ]…”
Section: Discussionmentioning
confidence: 99%